The Effect of Recast on Students Speaking Skill Based on Their Learning Strategies - Nurhartanto, Adhi (LLT Journal: A Journal on Language and Language Teaching, 2015)
Many studies have been conducted to find the effect of recast as a feedback on students. Some studies have also revealed that recast is found to be less effective. This study is aimed to find the effect of recast to students with different learning strategies in an EFL context in Indonesia. The study is conducted using quasi-experimental design. The research instruments include LLSQ questionnaire and speaking test. The results reveal that recast may be effective for students with certain dominance of learning strategies.